In search of ecclesial autonomyy : a church historical and church juridical study of developments in church polity in the Dutch Reformed Mission Church in South Africa (DRMC) and the Dutch Reformed Church in Africa (DRCA) from 1881-1994 - Van Rooi, Leslie Bernard (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DTh (Systematic Theology and Ecclesiology))--University of Stellenbosch, 2010.